ARTI DAN TUJUAN PENDIDIKAN MANUSIA DALAM MEMBENTUK KARAKTER DAN SOLUSI PADA KECERDASAN GENERASI MUDA - Swanto Yusni, Irfan; Ronadia, Ronadia; Safitri, Sani; Bahtiar Pamulaan, Alif (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The purpose of this article is to emphasize the importance of character education in forming a young generation who is intelligent, moral, and ready to face future challenges. The method used in this research is descriptive analytical with a library study approach, which collects data from various written sources to provide a deeper understanding of character education. The issues raised include deviant behavior among the younger generation caused by a character crisis and lack of character education, as well as teachers’ responsibilities in guiding students to develop positive character. The research findings indicate that character education does not only focus on academic achievement, but also on instilling moral and ethical values that can shape students’ positive behavior. In addition, this article identifies educational solutions that can be implemented to increase the intelligence of the younger generation, including education about the use of social media, religious values and pancasila, as well as the development of policies that support morality. Keywords: character education, young generation, education solutions